(untitled) (Indian Journal of Animal Production and Management, 2015)
Records of 729 Frieswal cows of Assam were utilized for the present study. The correlations of the FLMY with AFC, FLL, FDP and FCI were partitioned into direct and indirect effects. The numerical values of the coefficients assigned to each of the path showed maximum direct effect of FLL (0.645) on FLMY followed by that of FCI (0.548). The direct effects of AFC and FDP were found to be low (0.034 and – 0.132 respectively). The FLL had maximum total effects (0.662) on FLMY followed by FCI (0.238).